The Federal Voting Assistance Program and the Road Ahead Achieving Institutional Change Through Analysis and Collaboration - Greenfield, Victoria A. (RAND Corporation, 2015)
This report documents the Federal Voting Assistance Program's efforts to align its strategy and operations to better serve its mission and stakeholders, and strengthen its capacity to set its own course, greet change, and communicate its role in the voting community. The report shows the potential for substantial, timely change in a highly collaborative working relationship, rooted in a systematic and analytically grounded research design.